D‐Glucuronic Acid Coated Gd(IO3)3·2H2O Nanomaterial as a Potential T1 MRI‐CT Dual Contrast Agent. Issue 16 (12th April 2013) - Lee, Eun Jung; Heo, Woo Choul; Park, Jang Woo; Chang, Yongmin; Bae, Ji‐Eun; Chae, Kwon Seok; Kim, Tae Jeong; Park, Ji Ae; Lee, Gang Ho
Abstract: To date, only a few nanosystems have been investigated as T 1 MRI‐CT dual contrast agents. The T 1 MRI‐CT dual functionality of a material depends on its longitudinal water‐proton relaxivity ( r 1 ) and X‐ray absorption strength. We explored Gd(IO3 )3 · 2H2 O nanomaterial because Gd is the most powerful element for T 1 MRI contrast agents, and both Gd and I absorb X‐ray radiation; Gd absorbs X‐ray radiation ca. 2.5 times more strongly than I.D ‐Glucuronic acid coated Gd(IO3 )3 · 2H2 O nanomaterial showed a very large r 1 of 52.3 s –1  mM –1 ( r 2 / r 1 = 1.21), which could be ascribed to hydrated water molecules in the lattice. Its X‐ray absorption intensity was also stronger than those of commercial molecular iodine CT contrast agents. This result clearly suggests thatD ‐glucuronic acid coated Gd(IO3 )3 · 2H2 O nanomaterial is a potential T 1 MRI‐CT dual contrast agent. Abstract : D ‐Glucuronic acid coated Gd(IO3 )3 · 2H2 O nanomaterial is synthesized in one‐pot and its T 1 MRI‐CT dual imaging properties are investigated. It has a very large r 1 and strong X‐ray absorption, which are prerequisites for high‐performance T 1 MRI‐CT dual contrast agents.